Rapid prototyping tools for power electronic systems: demonstration with shunt active power filters - Jacobs, J.; Detjen, D.; Karipidis, C.-U.; De Doncker, R.W. (IEEE transactions on power electronics, 2004)
This paper presents three new rapid prototyping tools to develop power electronic systems. The effectiveness of these tools is demonstrated by designing and building a shunt active power filter. First, a digital signal processor (DSP) model to embed complex control algorithms has been created for detailed offline simulations with PSpice. This DSP model emulates the discrete behavior of digital control circuits. The control algorithms in the DSP model are implemented in C-code. Secondly, the control C-code can be downloaded to the ISEADSP for real-time execution. The ISEADSP is a universal DSP control board based on two 80 SHARC processors which execute control algorithms of various nature and highest complexity at 80 MFLOP per second. Thirdly, power electronic building blocks (PEBBs) based on IGBT devices were developed to build and analyze quickly different converter topologies. Combining these three rapid prototyping tools led to a significant reduction of development time of power electronic applications.